Food security and BMI status among adolescents in Kuantan, Pahang - Mohd Abu Bakar, Wan Azdie; Yahya, Noor Atirah; Sidek, Suriati; Ab Ghalib, Halimatun Saadiah; Mat Ya, Roselawati; Abdul Rahman, Rozlin (Karger Publishers, 2019)
Background/Aims: Food security can be defined as the availability of and accessibility to food, acquired in an acceptable means at any given time and place in a way that could maintain health and wellbeing. This study aimed to identify the food security status and the nutritional status of adolescents and to determine the associated factors. Methods: Five hundred and thirty secondary school students from district of Kuantan, Malaysia were measured for their weights and heights. A set of questionnaire containing two sections was used to obtain the sociodemographic data and food security information. The Radimer/Cornell Instrument (Malay version) was used to capture the severity of food insecurity. Results: The findings demonstrated that 23.4% of the respondents were food secure and 76.6% were food insecure, which were categorized into household food insecurity (31.5%), individual food insecurity (7.6%) and child hunger (37.5%). Furthermore, 60% have normal BMI-for-age, 9.2% were underweight, while 16.6% and 14.2% were overweight and obese. The prevalence of stunting was 11.7% while others were categorized as normal in terms of height-for-age z-score. Respondents with working mothers were found to be less likely to experience food insecurity compared to those with mothers who were not working (AOR 0.59; 95% CI: 0.34–0.97; p = 0.037). Conclusion: The high prevalence of food insecurity and increasing overweight and obesity incidents are a concern within this area. While food security element should be included in any intervention program addressing overweight and obesity, further research is needed to study the complex relationship between socio-demographic factors, food security and nutritional status.